The effect of SARS-CoV-2 mRNA vaccination on AMH concentrations in infertile women. Issue 4 (October 2022) - Horowitz, Eran; Mizrachi, Yossi; Ganer Herman, Hadas; Oz Marcuschamer, Einat; Shalev, Amir; Farhi, Jacob; Barber, Elad; Orna, Schwartz Harari; Raziel, Arieh; Weissman, Ariel
ABSTRACT: Research question: Does SARS-CoV-2 mRNA vaccination affect the ovarian reserve of infertile women undergoing IVF? Design: This was a prospective observational study at a single university-affiliated IVF unit that included infertile women aged 18–44 years who were undergoing IVF/intracytoplasmic sperm injection between November 2020 and September 2021, had received two doses of SARS-CoV-2 mRNA vaccination and had undergone measurement of baseline anti-Müllerian hormone (AMH) concentration within the 12 months preceding their recruitment. AMH concentrations before and after vaccination were evaluated and compared. Results: Overall, 31 women were included in the study. The median AMH concentrations before and after COVID-19 vaccine were comparable (1.7 versus 1.6 g/ml, respectively, P  = 0.96). No correlation was found between the participant's anti-COVID-19 antibody titre and the change in AMH concentration. Conclusions: SARS-CoV-2 mRNA vaccination does not adversely affect ovarian reserve, as shown by comparing serum AMH concentrations before and after vaccination. These findings may serve as a counselling tool for clinicians to reassure women undergoing fertility treatment that SARS-CoV-2 mRNA vaccination is safe.